2022
DOI: 10.1016/j.psj.2021.101542
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical control of poultry coccidiosis: a review

Abstract: Avian coccidiosis is a major parasitic disorder in chickens resulting from the intracellular apicomplexan protozoa Eimeria that target the intestinal tract leading to a devastating disease. Eimeria life cycle is complex and consists of intra- and extracellular stages inducing a potent inflammatory response that results in tissue damage associated with oxidative stress and lipid peroxidation, diarrheal hemorrhage, poor growth, increased susceptibility to other disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
95
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 135 publications
(97 citation statements)
references
References 192 publications
(220 reference statements)
2
95
0
Order By: Relevance
“…However, eliminating antibiotics from the animal diet reflected poorly on growth enhancement, FCR, and feed efficiency ( Puvača et al, 2019a ; Reda et al, 2020 ; Sheiha et al, 2020 ; Reda et al, 2021a ). Therefore, the use of natural compounds, such as probiotics ( Abd El‐Hack et al, 2020a ; Alagawany et al, 2021a ; El-Saadony et al, 2021a ), prebiotics ( Yaqoob et al, 2021 ; Abd El-Hack et al, 2022 ), essential oils ( Alagawany et al, 2021b ; El-Tarabily et al, 2021 ), herbal extracts ( Abou-Kassem et al, 2021 ; Saad et al, 2021a ), amino acids ( Abou-Kassem et al, 2021 ), green synthesized nanoparticles ( Abd El-Ghany et al, 2021 ; El-Saadony et al, 2021b , c , d ), bioactive peptides ( El-Saadony et al, 2021e , f ), safe, natural pigments ( Abdelnour et al, 2020a , b ; Ashour et al, 2021 ), bioactive medicinal plants ( El-Saadony et al., 2022 ), plant products ( El-Shall et al, 2022 ), and phytogenic compounds ( Abd El-Hack et al, 2020b ; Abd El‐Hack et al, 2021b ; Abdel-Moneim et al., 2022 ), for growth promotion and pathogen resistance became a trend and an alternative to antibiotics ( Simon et al, 2005 ; Stanaćev et al, 2011 ; Puvača et al, 2013 ; Alagawany et al, 2021c ).…”
Section: Introductionmentioning
confidence: 99%
“…However, eliminating antibiotics from the animal diet reflected poorly on growth enhancement, FCR, and feed efficiency ( Puvača et al, 2019a ; Reda et al, 2020 ; Sheiha et al, 2020 ; Reda et al, 2021a ). Therefore, the use of natural compounds, such as probiotics ( Abd El‐Hack et al, 2020a ; Alagawany et al, 2021a ; El-Saadony et al, 2021a ), prebiotics ( Yaqoob et al, 2021 ; Abd El-Hack et al, 2022 ), essential oils ( Alagawany et al, 2021b ; El-Tarabily et al, 2021 ), herbal extracts ( Abou-Kassem et al, 2021 ; Saad et al, 2021a ), amino acids ( Abou-Kassem et al, 2021 ), green synthesized nanoparticles ( Abd El-Ghany et al, 2021 ; El-Saadony et al, 2021b , c , d ), bioactive peptides ( El-Saadony et al, 2021e , f ), safe, natural pigments ( Abdelnour et al, 2020a , b ; Ashour et al, 2021 ), bioactive medicinal plants ( El-Saadony et al., 2022 ), plant products ( El-Shall et al, 2022 ), and phytogenic compounds ( Abd El-Hack et al, 2020b ; Abd El‐Hack et al, 2021b ; Abdel-Moneim et al., 2022 ), for growth promotion and pathogen resistance became a trend and an alternative to antibiotics ( Simon et al, 2005 ; Stanaćev et al, 2011 ; Puvača et al, 2013 ; Alagawany et al, 2021c ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the addition of plant extract from Bidens pilosa inhibited the penetration of parasites into intestinal cells in chickens [ 31 ]. Numerous studies show the ability of phytochemicals to prevent diseases or strengthen the immunity of chickens, but there is still a lack of information about the underlying mechanisms [ 8 , 14 , 16 , 22 , 23 , 32 , 33 ].…”
Section: Immunomodulatory Properties Of Bioactive Productsmentioning
confidence: 99%
“…Therefore, AGP alternatives are much needed to control NE and other diseases. The drug-free program used essential oil alternatives rather than in-feed antimicrobials and coccidiostats, which were used in conventional systems ( Grave et al, 2004 ; El-Shall et al., 2022 ). Therefore, this review throws light on C. perfringens virulence factors involved in the pathogenesis of NE, available vaccines and emphasizes the use of herbal medicine as an alternative to antibiotics for the control and prevention of NE in broiler chickens.…”
Section: Introductionmentioning
confidence: 99%